The Effect of Self-Confidence on Mental Toughness of Adolescent Pencak Silat Athletes - Naliza, Mifta; Wijayaningsih, Dian Estining; Hudaya, Abdillah Arju; Pebrian, Ryan; Firmansyah, Randy Adi; Alim, Abdul; Nurfadhila, Risti; Salafi, Muhammad Irvan Eva; Budiarti, Ratna (Jorpres (Jurnal Olahraga Prestasi), 2024)
Self-confidence is one of the variables that impact the development of mental toughness. This study aimed to determine the relationship between mental toughness and self-confidence in adolescent pencak silat athletes. The quantitative description method was used in this study. This study used a purposive sampling technique for the sample. The study population amounted to one hundred and fifty athletes, with a sample of fifty teenage athletes who were members of the martial arts clubs Persaudaraan Setia Hati Terate, Merpati Putih, and Perisai Diri. The data acquisition method carried out during this period consisted of questionnaires and observations. The instruments used in this study were Pratama's self-confidence scale and Sella's mental toughness scale. The data analysis method used simple regression with SPSS. The findings of this study indicate that the self-confidence of adolescent pencak silat athletes is in the "low" category by 14% (7 athletes), "medium" by 72% (36 athletes), and "high" by 14% (7 athletes). At the same time, the mental toughness of adolescent pencak silat athletes is in the "low" category by 20% (10 athletes), "medium" by 64% (32 athletes), and "high" by 16% (8 athletes). The findings of the linear regression analysis show an F value of 70.919 with a significance level of 0.000 <0.05. This indicates that the mental toughness variable (Y) is influenced by the self-confidence variable (X) in adolescent pencak silat athletes. Based on data analysis, the R-squared value is 0.596 if it is presented to 59.6%, which indicates that self-confidence affects the mental toughness of adolescent martial arts athletes. This study shows that self-confidence plays a vital role in the mental strength of adolescent martial arts athletes. Future research is recommended to expand the scope of research to include other aspects that impact athletes' mental toughness. The practical implication is the importance of targeted mental training to increase self-confidence and manage stress in adolescent martial arts athletes.